Health Service Utilization Patterns Among Health Equity Fund Beneficiaries at Khmer-Soviet Friendship Hospital - Rithea Ngeth; Duy Nguyen-Quang (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to analyze health service utilization patterns among Health Equity Fund beneficiaries at the Khmer–Soviet Friendship Hospital (KSFH), Phnom Penh, with a particular focus on the distribution of service types and the role of HEF in facilitating access to advanced healthcare services. Methodology: A descriptive quantitative study was conducted using secondary data obtained from the medical records unit of KSFH. Data were processed through standardized procedures, including editing, coding, processing, and cleaning. Descriptive (univariate) analysis was employed to examine the frequency and percentage distribution of healthcare service utilization across outpatient, inpatient, emergency, surgical, diagnostic, and maternal services. Main Findings: The findings revealed that outpatient services were the most frequently utilized by HEF beneficiaries (38%), followed by inpatient care (26%) and emergency services (18%). Surgical services accounted for 10% of total utilization, with orthopedic and general surgeries being the most common. Diagnostic services (7%) and maternal and child health services (5%) were also accessed, indicating improved access to both essential and specialized care. Novelty/Originality of this study: This study provides novel evidence by systematically mapping HEF beneficiaries’ healthcare utilization patterns at a major national referral hospital using a structured SOFFIIWIER-based data processing framework.